Performance evaluation of Chabro chicken under field condition - Maroof Ahmad; Sarita Devi; S B Singh; Narendra Singh (Journal of Livestock Biodiversity, 2025)
Desi chickens are traditionally reared by tribal and resource poor rural people of Lalitpur District of Uttar Pradesh. They rear desi birds with low egg and meat production under backyard system of management. Improved poultry breeds are an important to replace the desi birds for better returns. The present study was carried out on 105 day old chicks of Chabro breed under field condition. The body weight was recorded at weekly interval up to 16 weeks of age. The mean values of body weight at 0 days, 4th, 8th, 12th and 16th week of age were estimated as 34.72 ± 0.59, 548.30 ± 3.18, 1020.37 ± 5.47, 1822.51 ± 8.21 and 2474.06 ± 9.31 g, respectively in Chabro birds maintained under field condition. Age at first lay was found to be 162.35 ± 4.38 days and average annual egg production was recorded as 167.42 ± 4.65 eggs. Egg weight up to 40 weeks of age and the survivability of Chabrobirds was recorded as 53.28 ± 2.12 g and 92.25 percent, respectively under field condition.